Evaluation of the delivery time and adverse neonatal outcomes in urinary culture-positive preterm delivery and preterm premature rupture of membranes - Ozler, Sibel; Oztas, Efser; Solmaz, Derya; Guler, Basak G.; Ersoy, Ali Ozgur; Caglar, Ali T.; Danisman, Nuri (CUKUROVA UNIV, FAC MEDICINE, 2020)
Purpose: We aimed to investigate the relationship between adverse neonatal outcomes and the time period of labor in between urinary tract infection in preterm premature rupture of membranes (PPROM) to preterm labor (PL). Materials and Methods: We evaluated a total number of 1033 pregnant patients who admitted to our center between 2008 and 2014, with retrospective analysis. Study groups consisted of 446 PPROM and 587 PL patients who had urine cultures. Results: We determined cervical lengths which were measured by transvaginal ultrasonography, with OR = 0.806 and amniotic fluid index (AFI), OR = 0.961 in PPROM group, which had positive urine culture, and also cervical length OR = 0.862 in PL group which had positive urine culture and to be associated with shorter than seven days of delivery. Additionally, we determined that only the AFI, with OR = 0.982, to be associated with adverse neonatal outcomes in the PPROM group, having positive urine culture. Conclusion: AFI and cervical length can also be used to predict adverse neonatal outcomes and time of delivery in urine culture positive PPROM and PL patients.
Keywords: Preterm premature rupture of membranes; preterm birth; urinary system infection